Zircon U-Pb geochronology of the Cenozoic granitic mylonite along the Ailaoshan-Red river shear zone: New constraints on the timing of the sinistral shearing - Zi, Jianwei; Guo, X.; Yang, Y.; Liu, H. (Zhongguo Dizhi Daxue, 2016)
The Ailaoshan-Red River (ASRR) shear zone in SW China represents an important discontinuity believed to have accommodated eastward extrusion of the Tibetan Plateau in response to the collision of the Indian and Eurasian plates. The onset timing and duration of the ASRR sinistral strike-slip shearing have been hotly disputed. In this paper we present new zircon LA-ICP-MS U-Pb geochronological data from six syntectonic granitic mylonite and leucosomes samples from the ASRR shear zone. Our data reveal a metamorphic age of ~40 Ma, most likely suggesting the maximum age of the shearing initiation. Rocks showing syn-kinematic signatures yield crystallization ages of 38–22 Ma, with inherited components ranging from 716 to 108 Ma. These results, together with existing geological and geochronological data, indicate that the sinistral shearing along the ASRR zone probably began at 40 Ma, mainly activated at 29–22 Ma and lasted at least to ~22 Ma. Our data suggest a continuous extrusion between the Indochina and South China blocks during ~35–17 Ma. The ASRR sinistral shearing has accommodated large scale eastward displacement of the southeastern Tibetan syntaxis, and is likely responsible for the opening of the South China Sea.